PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V MATA PELAJARAN BAHASA INDONESIA DI MIS MUTIARA AULIA - Mira Ulandari; Tri Indah Kusumawati; Aufa Aufa (JOURNAL SAINS STUDENT RESEARCH, 2025)
The Problem Bassed Learning learning model is a learning model that focuses on the root of the problem and solving the problem. Problems can create conditions that encourage students to quickly solve them, but under certain conditions, students do not know how to solve them. This research was motivated by the lack of reading comprehension skills of class V students at MIS Mutiara Aulia. And this research aims to find out whether the Problem Bassed Learning learning model has an effect on improving students' reading comprehension skills. By using quantitative methods, researchers used two classes, namely the experimental class and the control class. And based on the final results of the research, the use of the Problem Based Learning learning model shows that there is a significant influence from the application of this model. This can be seen based on the average value of student learning outcomes using the Problem Based Learning learning model is 74.00, while the average value of learning outcomes using the conventional learning model is 37.9. Based on the results of the t test, it was obtained (9.471 ≥ 2.024).